Sustainability communication on social media : a study on the most sustainable brands in Finland - Artemova, Alexandra (2020)
Today’s consumers are becoming increasingly conscious about sustainability issues. For this reason, it is essentially important for companies to not only address these issues, but also transparently and authentically communicate about them. Social media created various possibilities for companies to communicate about their sustainability initiatives in an engaging way in order to establish a positive brand image and reputation, as well as meaningful organization-stakeholder relationships. The need for additional research on the topic of sustainability communication on social media led to development of the key objective of this thesis, which is to gain understanding of the role of social media in sustainability communication through the prism of the most sustainable Finnish brands. The research goal was achieved through studying the prior literature on the topic, as well as conducting both qualitative and quantitative content analyses. As a result of this study, it was possible to understand the main focus of social media communication of the sustainable Finnish brands, to analyse how sustainability-related messages are communication on social media of these brands, as well as to test whether sustainability communication on these brands’ social media affect stakeholder engagement. Also, as a result of achieving the key objective, practical recommendations for communicating sustainability initiatives were developed and proposed for the companies. Thus, the crucial importance of sustainability communication has been emphasized in both previous literature on the topic, as well as the empirical findings of this study. In addition to confirming the overall value of sustainability communication on the corporate social media channels, it has also been identified that companies acknowledge all three essentially important elements of sustainability and actively utilise different opportunities provided by social media for communicating sustainability in an interesting and engaging way. However, some differences related to the influence of sustainability-related content on stakeholder engagement were identified in this study as well.